Investigating the therapeutic utility of Olaparib in Metachromatic Leukodystrophy and Krabbe Disease - Mekhaeil, Marianna (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2024)
Leukodystrophies encompass a diverse group of genetically-based disorders that impact the development and preservation of myelin in the central nervous system's white matter. These conditions, affecting approximately 1 in 7,700 live births, exhibit significant variability in clinical presentation and disease progression, manifesting symptoms like motor dysfunction, cognitive impairment, and ataxia. Recent advancements in genetic medicine and imaging have shed light on the specific genetic and biochemical abnormalities associated with individual leukodystrophies, such as Metachromatic Leukodystrophy (MLD) and Krabbe disease (KD), which are characterized by the accumulation of toxic substances, sulfatide, and psychosine, respectively. Traditionally, it was believed that mutations in myelin- or oligodendrocyte-specific genes were solely responsible for leukodystrophies. However, contemporary research has expanded our understanding, revealing that these disorders are linked to defects in astrocytes, microglia, axons, and blood vessels. Despite limited knowledge of their underlying mechanisms, symptomatic treatments have been developed to alleviate some of the burdens associated with leukodystrophies. Nevertheless, effective cures for these conditions remain elusive, prompting exploration into addressing neuroinflammation as a promising therapeutic strategy. Poly (ADP-ribose) polymerase 1 (PARP-1) has emerged as a central player in chronic inflammation, operating not only in immune cells but also in astrocytes, endothelial cells, and fibroblasts, contributing to inflammation across various tissues. Some FDA-approved PARP-1 inhibitors, including Olaparib and Veliparib, have exhibited cytoprotective and anti-inflammatory effects in preclinical models of non-oncological diseases, such as neurological conditions (e.g., stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis), diabetes, and myocardial infarction. However, there is currently no direct evidence of PARP-1 involvement in leukodystrophies like KD or MLD, and no PARP-1 inhibitors are under clinical investigation for these conditions. In the context of MLD, research has focused on the interplay between sulfatide and Olaparib in astrocytes, which play a crucial role in inflammation and myelination. Studies have established a concentration-dependent model of sulfatide-induced astrocyte toxicity, with Olaparib effectively mitigating these effects. Sulfatide has also been found to induce impairments in ROS production, mitochondrial stress, and Ca2+ signaling in human astrocytes, all of which are alleviated by Olaparib treatment. Additionally, using an ex vivo model of murine-derived organotypic cerebellar slices, it was demonstrated that sulfatide induces demyelination, which can be attenuated by Olaparib treatment. In the case of KD, characterized by psychosine accumulation and chronic inflammation, a connection between psychosine toxicity and PARP-1 overactivation in both astrocytes and murine-derived organotypic cerebellar slices has been revealed. Psychosine-induced toxicity involves neuroinflammation, immune cell migration, ROS production impairments, Ca2+ signaling disturbances, demyelination, axonal degeneration, and oligodendrocyte loss. Olaparib treatment significantly mitigates the toxic effects of psychosine. In conclusion, this study provides compelling evidence that psychosine and sulfatide-induced neurotoxicity are mediated by PARP-1 activation, resulting in oligodendrocyte loss, heightened pro-inflammatory cytokine expression, increased ROS levels, and enhanced recruitment of NK and T cells. Furthermore, the findings suggest that Olaparib treatment may hold therapeutic potential in alleviating toxin-induced pathology in both MLD and KD. This research underscores the importance of exploring novel treatment avenues for rare demyelinating diseases and the potential of PARP-1 inhibitors as a promising therapeutic approach.
APPROVED